SPECIFIC FEATURES OF NATIONAL AND REGIONAL POLICIES IN CYBER SECURITY - Kotukh, Yevhen (Theory and Practice of Public Administration, 2019)
The world has a long history of counteracting crime, on-line wars and challenges. Since the public sector has to be ready to respond to cyberattacks, elaboration of practical counteraction measures becomes an urgent task.The paper considers an organizational mechanism and ways to counteract cyber threats. The international practices of getting public-administrative subjects involved in cyber security activities through a variety of legal acts and operating procedures have been analyzed. The above-mentioned measures are quite varied, which is stipulated by the extent of open access to public information, e-government sophistication, cybercrime incidence, previous experience of fighting cyber threats, as well as public opinion and public involvement. Information and knowledge about the public sector are created, changed, transferred and expanded to meet the social needs. E-government digitizes certain processes and results, changing them potentially in the ways which are not always predictable or appropriate for either the internal needs of the public sector or public service consumers. Thus, the consequences may be precarious. Therefore, it is expedient to identify the advantages and flaws of e-government and its capacity for counteracting cybercrime in each specific country.It has been proved that creation of public-private partnerships can become a more effective response of the national and regional policies to cyber security challenges. It is in this format that measures for enhancement of cyberspace cooperation can be used in order to provide a proper component of the national security of Ukraine.For Ukraine, finding the middle ground among control, openness and security is topical. Under these conditions, both the technicality of the issue and human behaviour should be given an increased attention to. Consideration of the said aspects should lay the basis for creation of public-private partnerships and raise the effectiveness of the national and regional policies in their response to cyber security challenges. It is also important to fully understand the ratio between the cyberthreat-related risks and benefits of using the system chosen to counteract them.